Alcohol-Related Sexual Consequences during the Transition from High School to College - Orchowski, Lindsay M. (2011)
Alcohol use and risky sexual behavior are significant problems on college campuses. Using a prospective design, the present study sought to explore the relationship between alcohol use and experience of alcohol-related sexual consequences (ARSC) during the transition from high school to the first year of college. During the senior year of high school, and following the first year of college, participants completed assessments of alcohol use, problem drinking behavior, ARSC, and potential influences on drinking behaviors, including parental knowledge of alcohol use, peer influences, motivation for alcohol use, and mood state. Data indicated that 29% of men and 35% of women indicated some form of ARSC during the last year of high school, rates that increased by 6-7% for the first year of college (36% of men and 41% of women). The onset or recurrence of ARSC in college was not explained by differential increases in alcohol use between high school and college. Low levels of positive affect, low motivation to consume alcohol to cope, and high levels of peer alcohol use were associated with repeated ARSC in high school and college; whereas drinking to enhance positive affect and low parental knowledge of alcohol use were associated with the onset of such consequences in college. Implications for intervention are discussed.